Changing Policy Environments in Europe and the Resilience of the Third Sector - Pape, Ulla; Brandsen, Taco; Pahl, Joachim Benedikt; Pieliński, Bartosz; Baturina, Danijel; Brookes, Nadia; Chaves-Ávila, Rafael; Kendall, Jeremy; Matančević, Jelena; Petrella, Francesca; Rentzsch, Christina; Richez-Battesti, Nadine; et al. (Voluntas (Manchester, England), 2020)
In the article, we analyse the impact of changing policy environments on the development of the third sector in Europe. Based on the results of systematic comparative research in eight European countries (Austria, Croatia, France, Germany, the Netherlands, Poland, Spain and the UK), we identify commonalities and differences. In a three-step analysis, we examine policy changes, effects on the third sector and responses by third sector organizations (TSOs) in the social domain. Overall, the third sector in Europe has proven resilient. However, not only have public and private funding decreased, the process for acquiring such funding has become more demanding for TSOs, as have requirements to be accountable. There are signs of a proliferation of more market-based, hybrid organizations. Despite this general trend towards marketization, the impact of policy changes varies across Europe with TSOs being better equipped to adapt and survive in countries where collaborative ties between the state and the third sector have traditionally been strong.